Electroconvulsive therapy decreases striatal dopamine transporter binding in patients with depression: A positron emission tomography study with [18F]FE-PE2I. (30th July 2020) - Masuoka, Takahiro; Tateno, Amane; Sakayori, Takeshi; Tiger, Mikael; Kim, WooChan; Moriya, Hiroki; Ueda, Satoshi; Arakawa, Ryosuke; Okubo, Yoshiro
Highlights: Previous studies suggested that dopaminergic neurotransmission plays a crucial role in the mechanism of the action of ECT. Eight patients with major depressive episodewere examined with [ 18 F]FE-PE2I positron emission tomography (PET)at pre-and post-ECT. Striatal DAT- binding potential (BPND )of all patients was reduced, with an average change ratio of DAT-BPND of-13.1±5.6%. The DA nervous system is part of themechanism of action of ECT. Abstract: Electroconvulsive therapy (ECT) is an effective treatment for major depression. Previous studies suggested that dopaminergic neurotransmission plays a crucial role in the mechanism of the action of ECT. Since dopamine transporters (DAT) regulate extracellular dopamine concentration, DAT represents an interesting target for the study of the mechanism of action of ECT. Eight inpatients (7 patients with major depressive disorder and 1 patient with bipolar disorder with a DSM-IV diagnosis) received a series of 7–15(11.3±5.2) bilateral ECT sessions.The severity of symptoms was assessed using the 21-item Hamilton Depression Rating Scale (HDRS) and Clinical Global Impression-Severity (CGI-S). All patients were examined with [ 18 F]FE-PE2I positron emission tomography (PET) at pre-ECT, after the 10 th ECT, and at post-ECT. Striatal DAT-binding potential (BPND ) of all patients was reduced, with an average change ratio of DAT-BPND of -13.1±5.6%. In the 2 cases with 15 ECT sessions, the ratio change of DAT-BPND after the 15th ECT was larger than that after the 10th ECT. Also, HDRS and CGI-S were reduced. These results indicate that the dopamine nervous system is part of themechanism of action of ECT.